2014
DOI: 10.1371/journal.pone.0088837
|View full text |Cite
|
Sign up to set email alerts
|

Strong Genome-Wide Selection Early in the Evolution of Prochlorococcus Resulted in a Reduced Genome through the Loss of a Large Number of Small Effect Genes

Abstract: The smallest genomes of any photosynthetic organisms are found in a group of free-living marine cyanobacteria, Prochlorococcus. To determine the underlying evolutionary mechanisms, we developed a new method to reconstruct the steps leading to the Prochlorococcus genome reduction using 12 Prochlorococcus and 6 marine Synechococcus genomes. Our results reveal that small genome sizes within Prochlorococcus were largely determined shortly after the split of Prochlorococcus and Synechococcus (an early big shrink) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 52 publications
7
37
0
Order By: Relevance
“…Reductive evolution is known to occur in a number of settings, including intracellular symbiosis (18,53), intracellular pathogenesis (54), and free-living pelagic microbes (55). In strictly intracellular organisms, reduction is thought to occur due to genetic drift as a consequence of genetic isolation and strict vertical transmission, low effective population sizes, and frequent bottlenecks (18).…”
Section: Discussionmentioning
confidence: 99%
“…Reductive evolution is known to occur in a number of settings, including intracellular symbiosis (18,53), intracellular pathogenesis (54), and free-living pelagic microbes (55). In strictly intracellular organisms, reduction is thought to occur due to genetic drift as a consequence of genetic isolation and strict vertical transmission, low effective population sizes, and frequent bottlenecks (18).…”
Section: Discussionmentioning
confidence: 99%
“…First, the minimum effect size required for a mutation to be 'seen' by natural selection is inversely related to the effective population size. Therefore, even very small fitness benefits can be selected in the very large populations typical of freeliving microbes, allowing efficient 'streamlining' of genomes [2,76]. Second, microbes frequently gain new functions via HGT, but when first acquired these functions are poorly integrated into the pre-existing genome [77].…”
Section: How Much Do Average Genes Cost?mentioning
confidence: 99%
“…Free-living bacteria with small genomes discovered to date tend to live in nutrient-poor marine environments. Even cultured isolates can have small genomes, including strains of Prochlorococcus marinus (the abundant photosynthetic species with genomes as small as 1.64 Mb 116 ) and culturable members of SAR11, a diverse clade characterized by small (average 1.34 Mb), AT-rich genomes. 117, 118 Single-cell genomics of bacteria in oligotrophic environments have revealed that uncultured representatives have even smaller (e.g., an estimated 0.61 Mb for strain AAA076-M08 119 ) and, interestingly, more AT-rich genomes than related cultured isolates.…”
Section: Genome Size and Structurementioning
confidence: 99%
“…While diverse mechanisms may underlie genome reduction in free-living bacteria, 116 adaptation has been emphasized. Under a model of adaptive genome reduction, often phrased as genome streamlining , smaller genomes may be advantageous, particularly in nutrient-poor environments where fitness is determined by competition for scarce resources.…”
Section: Genome Size and Structurementioning
confidence: 99%